TANGGUNG JAWAB PERUSAHAAN MULTINASIONAL DALAM FOREIGN DIRECT INVESTMENT - Ully Puspita Rana, Sarah (Universitas Ekasakti, 2023)
Foreign Direct Investment is an international capital flow where companies from one country establish or expand their companies in other countries. Therefore, there is not only a transfer of resources, but also the exercise of control over companies abroad. In Foreign Direct Investment there are parties who have legal relations. The party is the Multinational Corporation or Multinational Company and the Host State or host country. Foreign Direct Investment has benefits for the Host State, some of which are technology transfer, economic improvement, employment opportunities, foreign exchange reserves, and industrial growth. The purpose of this study is to analyze the implementation of the responsibilities of multinational companies in foreign direct investment and the responsibilities of multinational companies that violate investment agreements against national law. This research is a juridical-normative legal research with statutory and conceptual approaches. The sources of legal entities used are in the form of primary and secondary legal materials which are collected using inventory techniques and then analyzed normatively in order to interpret the law (interpretation). The results of the study found that the Implementation of Multinational Company Responsibilities can be seen in the Indonesian legal system which is regulated in Law Number 25 of 2007 concerning Investment, Law Number 40 of 2007 concerning Limited Liability Companies. According to Indonesian legal provisions, multinational companies that violate investment agreements against national law can be subject to sanctions. Sanctions can be in the form of criminal or administrative sanctions